Predictors and neurological consequences of periprocedural cerebrovascular events following transcatheter aortic valve implantation with self-expanding valves - Suhai, Ferenc Imre; Varga, Andrea; Szilveszter, Bálint; Nagy-Vecsey, Milán; Apor, Astrid; Nagy, Anikó Ilona; Kolossváry, Márton; Karády, Júlia; Bartykowszki, Andrea; Molnár, Levente; Jermendy, Ádám L.; Panajotu, Alexisz; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims To evaluate the patient- and procedure-related predictors of transcatheter aortic-valve implantation (TAVI)-associated ischemic brain lesions and to assess the effect of silent cerebral ischemic lesions (SCIL) on neurocognitive function. Methods and results We investigated 113 consecutive patients with severe aortic stenosis who underwent brain magnetic resonance imaging (MRI) within a week following TAVI. To assess periprocedural cerebral ischemic lesions, diffusion-weighted MRI was utilized. We used multivariate linear regression to identify the independent predictors of TAVI-related ischemic lesion volume (ILV) and periprocedural stroke. Neurocognitive evaluation was performed before and following TAVI at 6-month and one-year follow-up. Following TAVI, a total of 944 new cerebral ischemic lesions were detected in 104 patients (92%). The median ILV was 257 μl (interquartile range [IQR]:97.1–718.8μl) with a median lesion number of 6/patient [IQR:2–10]. The majority of ischemic lesions were clinically silent (95%), while 5% of the lesions induced a stroke, which was confirmed by MRI. Predilatation (β = 1.13[95%CI:0.32–1.93], p = 0.01) and the number of valve positioning attempts during implantation (β = 0.28[95%CI:0.06–0.50], p = 0.02) increased the log-transformed total ILV. Predilatation (OR = 12.04[95%CI:1.46–99.07], p = 0.02) and alternative access routes (OR = 7.84[95%CI:1.01–61.07], p = 0.02) were associated with stroke after adjustments for comorbidities and periprocedural factors. The presence of SCILs were not associated with a change in neurocognitive function that remained stable during the one-year follow-up. Conclusion While periprocedural ischemic lesions are frequent, most of them are clinically silent and might not impact the patients' neurocognitive function. The number of valve positioning attempts, predilatation, and alternative access routes should be taken into consideration during TAVI to reduce the ILV and risk for stroke.